The recharge of glacial meltwater and its influence on the geochemical evolution of groundwater in the Ordovician-Cambrian aquifer system, northern part of the Baltic Artesian Basin. (September 2016) - Pärn, Joonas; Raidla, Valle; Vaikmäe, Rein; Martma, Tõnu; Ivask, Jüri; Mokrik, Robert; Erg, Katrin
Abstract: The geochemical evolution of groundwater in the Ordovician-Cambrian aquifer system in the northern part of the Baltic Artesian Basin (BAB) illustrates how continental glaciations have influenced groundwater systems in proglacial areas. The aquifer system contains water that has originated from various end-members: recent meteoric water, glacial meltwater and relict Na-Cl brine. The saline formation water that occupied the aquifer system prior to the glacial meltwater intrusion has been diluted by meltwaters of advancing-retreating ice sheets. The diversity in the origin of groundwater in the aquifer system is illustrated by a wide variety in δ 18 O values that range from −11‰ to −22.5‰. These values are mostly depleted with respect to values found in modern precipitation in the area. The chemical and isotopic composition of groundwater has been influenced by mixing between waters originating from different end-members. In addition, the freshening of a previously saline water aquifer due to glacial meltwater intrusion has initiated various types of water-rock interaction (e.g. ion exchange, carbonate mineral dissolution). Highlights: δ 18 O values suggests that the groundwater has partially originated from glacial meltwater recharge. Three-component mixing trend involving modern precipitation, glacial meltwater and Na-Cl brine end-members is evident. Waters originating from glacial meltwater recharge have been influenced by ion exchange. Negative correlation between pH values and HCO3 − concentrations supports the glacial origin of waters.